2011
DOI: 10.1111/j.1745-4530.2009.00367.x
|View full text |Cite
|
Sign up to set email alerts
|

Process Optimization for a Novel Kefir Candy With High Probiotic Viability

Abstract: Kefir, a beverage produced by the action of lactic acid bacteria (LAB), yeasts and acetic acid bacteria on milk, has a long tradition of offering health benefits. The objective of this research was to optimize the best formula for producing the kefir candy with maximum viabilities of LAB and yeasts using the response surface modeling and the sequential quadratic programming (SQP) method. In this study, milk was mixed with 5% kefir grains and incubated at 20C for 24 h. The samples were blended with lyoprotectan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
5
0
3
Order By: Relevance
“…Kefir microorganisms can produce singlecell proteins by the aerobic fermentation of cheese whey (Paraskevopoulou et al, 2003). Chen, Kuo, Shiu, and Chen (2011) produced a new kefir candy with health benefits and good flavour. Magalhaes et al (2011b) determined the chemical and sensory properties of cheese whey-based kefir beverages using grains as a starter culture, and indicated their potential.…”
Section: Introductionmentioning
confidence: 99%
“…Kefir microorganisms can produce singlecell proteins by the aerobic fermentation of cheese whey (Paraskevopoulou et al, 2003). Chen, Kuo, Shiu, and Chen (2011) produced a new kefir candy with health benefits and good flavour. Magalhaes et al (2011b) determined the chemical and sensory properties of cheese whey-based kefir beverages using grains as a starter culture, and indicated their potential.…”
Section: Introductionmentioning
confidence: 99%
“…High values of coefficient of determination ( R 2 ) (close to one) were indicating a high proportion of variability accounted for model terms and adequately explained by the models (Madamba, 2002; Montgomery, 1984). The non‐significant “Lack of fit” for each model was also indicating good fit of experimental data to regression model (Chen, Kuo, Shiu, & Chen, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…SQP was also conducted to search for optimal results. Chen et al (2007Chen et al ( , 2011 indicated that combination of RMS and SQP was an effective way to obtain the optimal manufacturing conditions for a new product development. In this study, a combination of 18.7% maltodextrin and 12.5% gum arabic as coating materials yielded the highest C1L survival under spray drying.…”
Section: Discussionmentioning
confidence: 99%